Territórios de vida e trabalho dos pequenos produtores de queijo da Serra da Canastra: um estudo sobre a relação entre produção camponesa e espaços naturais protegidos nas nascentes do rio São Francisco, Minas Gerais - Barbosa, Cristiano (2007)
s research deals with the relationships between peasant agriculture and protected environmental areas. The terrain, as central issue of investigation in Geography, is present in studies aimed at the understanding of the dynamics involving the social and productive aspects of occupied spaces. In this research scenario it is analyzed the relationship between small-scale dairy producers and the National Park of Serra da Canastra. This environmental unity, located in the central west region of the state of Minas Gerais, Brazil, was created in 1972, by the act of the law 70.355, encompasses 200.000 ha but nowadays occupies a little more than a third of its original area. The proposal to expand the area of the park presented in 2005 provoked a conflict between the local population and the environmental Brazilian agency (Brazilian Environmental and Renewable Natural Resources Institute - IBAMA). The government agency approved a new plan to manage the area and ratify the need to regulate the original area as well as to establish a 10 km land stripe encircling the park. Ecological and Rural tourism exploitation, along with a more modern line of cheese production aiming at obtaining the origin stamp certification, are pointed out as economics strategies that can be associated towards both natural resources conservation and new generation of work and income for peasant families. The ones, who support the thesis that the withdrawn of people out of the park would not guarantee their protection, believe that all interests, environmental, farming, cattle raising and tourism may be conciliatory. Our objective is to verify under what political, economical and social conditions the peasants could remain in such extended territory. This research points out the main obstacles to be overcome so that the peasants can live in this territory.